All-solid-state air battery and preparation method thereof
By using redox polymer materials and proton exchange membranes with phenolic hydroxy-quinone systems in all-solid air batteries, combined with porous catalysts, the safety hazards and cycle performance problems of existing solid lithium-air batteries are solved, and high energy density, safe and environmentally friendly battery performance is achieved.
Patent Information
- Application Number
- CN202411751969.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
During the industrialization of existing solid-state lithium-air batteries, there are problems with safety hazards and cyclic performance impacts caused by lithium oxide crystallization.
Using the structure of an all-solid air battery, hydrogen ion conversion and electrochemical reactions during the charge and discharge process are achieved by using a redox polymer material of a phenolic hydroxy-quinone system in the anode, combined with a proton exchange membrane and a porous catalyst of platinum carbon or palladium carbon.
The safety problem of liquid electrolyte is solved, the weight of the cathode is reduced, the energy density is improved, the capacity retention rate of 500 weeks of cycle charge and discharge is greater than 85%, and the battery is safe and environmentally friendly when in use.
Smart Images

Figure CN119560600A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to an all-solid-state air battery and a preparation method thereof. Background Art
[0002] Air battery is a new type of battery. It has a theoretical energy density of 3500mWh / g, far exceeding the current ternary lithium battery and lithium iron phosphate battery.
[0003] The principle of all-solid-state air batteries is to use the oxygen in the air to react electrochemically with hydrogen from the anode to generate electric current. There are two similar types of batteries: hydrogen fuel cells and lithium (zinc) air batteries. These two types of batteries are not the same as all-solid-state air batteries. Hydrogen fuel cells are more like power plants and cannot be recharged. Lithium-air batteries use liquid electrolytes and use the electrochemical reaction of metals and oxygen to generate electric current. Patent CN105870449 discloses a solid-state lithium-air battery, but during industrialization, the electrochemical reaction between lithium and oxygen will produce lithium oxide crystals, which will be coated on the outside of the cathode material to form crystallization, thereby creating safety hazards and affecting the cycle performance. Therefore, it is of great significance to prepare a new air battery. Summary of the invention
[0004] To solve the above problems, an object of the present invention is to provide an all-solid-state air battery and a method for preparing the same.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0006] An all-solid-state air battery comprises a housing, an anode and a cathode, wherein the anode and the cathode are arranged in the housing; a proton exchange membrane is arranged between the anode and the cathode, and the anode is connected to the cathode through a tab and a wire; the other side of the cathode is connected to a gas diffusion layer;
[0007] The anode is made of a redox polymer material containing a phenolic hydroxyl group or a quinone group structure;
[0008] The cathode is platinum carbon, palladium carbon, or a porous catalyst loaded with a platinum alloy or a palladium alloy.
[0009] The gas diffusion layer is carbon fiber cloth or metal filter mesh.
[0010] The shell is provided with an air inlet and an air outlet.
[0011] The proton exchange membrane is a perfluorosulfonic acid proton exchange membrane.
[0012] The anode is prepared according to the following method:
[0013] 1) Mixing a phenolic hydroxyl-containing compound and an aldehyde-containing compound, adding an acid or base catalyst, stirring and mixing evenly, heating to 50-120° C. and reacting for 0.5-20 hours to obtain a reaction solution;
[0014] 2) adding the reaction solution obtained in step 1) to the porous conductive material, stirring and kneading, and after sufficient absorption and infiltration, heating to 95-110° C. for curing, drying at 130° C., and then crushing to a particle size D50 of 2-20 μm to obtain a redox polymer material;
[0015] 3) The redox polymer material, conductive agent, adhesive and water obtained in step 2) are uniformly mixed, stirred for 10 to 24 hours, coated on a copper foil or aluminum foil with a tab, and dried to obtain an anode.
[0016] In step 1), the molar ratio of the phenolic hydroxyl-containing compound to the aldehyde-containing compound is 1-2:1-3.
[0017] The phenolic hydroxyl compound in step 1) is one or two of phenol, hydroquinone, catechol, resorcinol, phloroglucinol, 1,2,4,5-pyrogallol, salicylic acid, gallic acid, tannic acid, biphenyldiphenol, biphenyltetraphenol, biphenylhexaphenol, naphthol, naphthalene diphenol and naphthalene tetraphenol.
[0018] The aldehyde-containing compound in step 1) is one or two of formaldehyde, acetaldehyde and paraformaldehyde.
[0019] The amount of the acid or base catalyst added in step 1) is 0.1 to 2 times the total mass of the phenolic hydroxyl-containing compound and the aldehyde-containing compound.
[0020] In step 1), the acid is one or two of hydrochloric acid, phosphoric acid, sulfuric acid and oxalic acid; the base is one or two of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, ammonia water, urotropine, trimethylamine and triethylamine.
[0021] In step 2), the volume mass ratio of the reaction solution to the porous conductive material is 0.2 to 1.5:1.
[0022] The porous conductive material in step 2) is porous carbon or porous alloy.
[0023] The mass ratio of the redox polymer material, the conductive agent, the adhesive and the water in step 3) is 85-95:1-5:1-5:50-200.
[0024] In step 3), the conductive agent is one or two of conductive carbon black, conductive graphite, graphene and carbon nanotubes, and the binder is one or two of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile and polyacrylic acid.
[0025] The method for preparing the all-solid-state air battery comprises the following steps:
[0026] The anode, proton exchange membrane, cathode and gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] The present invention creates an all-solid-state air battery for the first time. Compared with existing batteries: (1) The present invention adopts a structure similar to that of a hydrogen fuel cell, but the anode adopts a redox polymer structure, and charging and discharging are achieved by gaining and losing hydrogen ions at the anode; while hydrogen fuel cells cannot be charged; (2) Compared with lithium-air or zinc-air batteries, the safety problem of liquid electrolyte is solved; (3) Compared with the solid-state lithium batteries that are currently being widely studied, the weight of the cathode of the present invention is greatly reduced. The solid-state air battery uses air as the cathode, and only a small amount of catalyst is required for the cathode. The weight of the cathode of the lithium battery accounts for about 60% of the battery cell, so the air battery prepared by the present invention has a higher energy density.
[0029] The preparation process of the redox polymerization anode is disclosed for the first time in the all-solid-state air battery of the present invention. The anode adopts a redox polymer active material of the phenolic hydroxyl-quinone system. During the charge and discharge process, the anode realizes conversion between the phenolic hydroxyl group and the quinone group by gaining and losing hydrogen ions. The particle size D50 of the redox polymer active material prepared by the present invention is between 2 and 20 um. If the particle size is too large, the rate performance will be affected; if the particle size is too small, the first effect will be affected. During discharge, the phenolic hydroxyl group loses hydrogen ions to form a benzoquinone structure. The hydrogen ions are transferred to the cathode through the proton exchange membrane. Under the action of the transition metal catalyst, they react electrochemically with oxygen in the air to generate current. During charging, water molecules in the humid air generate hydrogen ions under the action of the transition metal catalyst. They migrate to the anode through the proton exchange membrane under the electric field, and the benzoquinone structure of the anode is converted into a phenolic hydroxyl structure for electricity storage.
[0030] The all-solid-state air battery of the present invention has a higher energy density than the common lithium batteries or lead-acid batteries on the market. The energy density of the prepared all-solid-state air battery exceeds 800mWh / g. The capacity retention rate is greater than 85% after 500 cycles of charge and discharge. Moreover, the battery is safe and environmentally friendly when used, and can be applied to energy storage, electric vehicles, electric ships, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the structure of the all-solid-state air battery of the present invention;
[0032] Figure 2 This is a particle size distribution diagram of the redox polymer material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to better understand the technical solution of the present invention, the above content of the present invention is further described in detail below through specific implementation methods in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above content of the present invention belong to the scope of the present invention.
[0034] like Figure 1 As shown, the all-solid-state air battery of the present invention comprises a shell, an anode and a cathode, wherein the anode and the cathode are arranged in the shell; a proton exchange membrane is arranged between the anode and the cathode, and the anode is connected to the cathode through a pole ear and a wire; the other side of the cathode is connected to a gas diffusion layer; and an air inlet and an air outlet are arranged on the shell.
[0035] Example 1 Preparation of anode:
[0036] 100g of resorcinol and 150g of 37% formaldehyde were stirred and mixed evenly, and then 50g of oxalic acid was added, stirred and mixed evenly, and heated to 80°C for reaction for 5h to obtain a reaction solution; 100mL of the reaction solution was added to 200g of porous carbon, stirred and kneaded evenly, and after sufficient absorption and infiltration, heated to 95°C for curing, dried at 130°C, and then crushed to a particle size D50 of 7.2um to obtain a redox polymer material, and its particle size detection spectrum is as follows Figure 2 As shown; 92g of redox polymer material, 4g of conductive carbon black, 2g of carboxymethyl cellulose, 2g of styrene-butadiene rubber and 150g of water were mixed evenly, stirred for 10h, coated on an aluminum foil with a pole ear, and dried to obtain an anode.
[0037] Preparation of all-solid-state air battery:
[0038] The anode, perfluorosulfonic acid proton exchange membrane, platinum-carbon cathode and carbon fiber cloth gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0039] Example 2 Preparation of anode:
[0040] 100g of gallic acid and 130g of 37% formaldehyde are stirred and mixed evenly, and then 40g of concentrated hydrochloric acid is added, stirred and mixed evenly, and heated to 90°C for reaction for 2h to obtain a reaction solution; 100mL of the reaction solution is added to 130g of porous carbon, stirred and kneaded, and after sufficient absorption and infiltration, heated to 105°C for curing, dried at 130°C, and then crushed to a particle size D50 of 8.2um to obtain a redox polymer material; 90g of the redox polymer material, 5g of conductive graphite, 3g of carboxymethyl cellulose, 2g of polyvinyl pyrrolidone and 160g of water are mixed evenly, stirred for 18h, coated on a copper foil with a pole ear, and dried to obtain an anode.
[0041] Preparation of all-solid-state air battery:
[0042] The anode, perfluorosulfonic acid proton exchange membrane, palladium carbon cathode and metal filter gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0043] Example 3 Preparation of anode:
[0044] 100g of phloroglucinol and 150g of 37% formaldehyde are stirred and mixed evenly, and then 30g of sodium hydroxide is added, stirred and mixed evenly, and heated to 70°C for reaction for 5h to obtain a reaction solution; 100mL of the reaction solution is added to 200g of porous carbon, stirred and kneaded, and after sufficient absorption and infiltration, heated to 95°C for curing, dried at 130°C, and then crushed to a particle size D50 of 6.5um to obtain a redox polymer material; 94g of the redox polymer material, 3g of graphene, 1.5g of polyacrylonitrile, 1.5g of styrene-butadiene rubber and 100g of water are mixed evenly, stirred for 20h, coated on a copper foil with a pole ear, and dried to obtain an anode.
[0045] Preparation of all-solid-state air battery:
[0046] The anode, perfluorosulfonic acid proton exchange membrane, platinum-carbon cathode and carbon fiber cloth gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0047] Example 4 Preparation of anode:
[0048] 100 g of 1,2,4,5-benzeneteterol and 160 g of 37% formaldehyde were stirred and mixed evenly, and then 50 g of ammonia water was added, stirred and mixed evenly, and heated to 70°C for reaction for 3 hours to obtain a reaction solution; 100 mL of the reaction solution was added to 180 g of porous alloy, stirred and kneaded, and after sufficient absorption and infiltration, heated to 105°C for curing, dried at 130°C, and then crushed to a particle size D50 of 9.1 um to obtain a redox polymer material; 85 g of the redox polymer material, 5 g of carbon nanotubes, 1.5 g of carboxymethyl cellulose, 2.5 g of polyacrylic acid and 100 g of water were mixed evenly, stirred for 12 hours, coated on a copper foil with a pole ear, and dried to obtain an anode.
[0049] Preparation of all-solid-state air battery:
[0050] The anode, perfluorosulfonic acid proton exchange membrane, palladium-carbon cathode and carbon fiber cloth gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0051] Example 5 Preparation of anode:
[0052] 100g of naphthalene diol and 120g of 37% formaldehyde are stirred and mixed evenly, and then 45g of sodium carbonate is added, stirred and mixed evenly, and heated to 70°C for reaction for 3h to obtain a reaction solution; 100mL of the reaction solution is added to 150g of porous carbon, stirred and kneaded, and after sufficient absorption and infiltration, heated to 95°C for curing, dried at 130°C, and then crushed to a particle size D50 of 10um to obtain a redox polymer material; 85g of the redox polymer material, 1g of conductive carbon black, 1g of carboxymethyl cellulose and 90g of water are mixed evenly, stirred for 16h, coated on an aluminum foil with a pole ear, and dried to obtain an anode.
[0053] Preparation of all-solid-state air battery:
[0054] The anode, perfluorosulfonic acid proton exchange membrane, platinum-carbon cathode and stainless steel filter gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0055] Example 6 Preparation of anode:
[0056] 100g of naphthalene tetraphenol and 160g of 37% formaldehyde are stirred and mixed evenly, and then 40g of urotropine are added, stirred and mixed evenly, and heated to 100°C for reaction for 5h to obtain a reaction solution; 100mL of the reaction solution is added to 180g of porous carbon, stirred and kneaded, and after sufficient absorption and infiltration, heated to 105°C for curing, dried at 130°C, and then crushed to a particle size D50 of 8.2um to obtain a redox polymer material; 91g of the redox polymer material, 4g of conductive carbon black, 3g of polyvinyl pyrrolidone, 2g of styrene-butadiene rubber and 100g of water are mixed evenly, stirred for 15h, coated on an aluminum foil with a pole ear, and dried to obtain an anode.
[0057] Preparation of all-solid-state air battery:
[0058] The anode, perfluorosulfonic acid proton exchange membrane, palladium carbon cathode and carbon fiber gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0059] Example 7 Preparation of anode:
[0060] 100 g of hydroquinone and 44 g of acetaldehyde are stirred and mixed evenly, and then 40 g of potassium hydroxide is added, stirred and mixed evenly, and heated to 70°C for reaction for 2 hours to obtain a reaction solution; 100 mL of the reaction solution is added to 150 g of porous carbon, stirred and kneaded, and after sufficient absorption and infiltration, heated to 100°C for curing, dried at 130°C, and then crushed to a particle size D50 of 7.4 um to obtain a redox polymer material; 93 g of the redox polymer material, 4 g of conductive graphite, 1.5 g of polyacrylic acid, 1.5 g of styrene-butadiene rubber and 150 g of water are mixed evenly, stirred for 18 hours, coated on an aluminum foil with a pole ear, and dried to obtain an anode.
[0061] Preparation of all-solid-state air battery:
[0062] The anode, perfluorosulfonic acid proton exchange membrane, platinum-carbon cathode and carbon fiber gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0063] Example 8 Preparation of anode:
[0064] 100 g of catechol and 73 g of acetaldehyde were stirred and mixed evenly, and then 100 g of ethylenediamine was added, stirred and mixed evenly, and heated to 80° C. for reaction for 3 hours to obtain a reaction solution; 100 mL of the reaction solution was added to 140 g of porous carbon, stirred and kneaded evenly, and after sufficient absorption and infiltration, heated to 105° C. for curing, dried at 130° C., and then crushed to a particle size D50 of 9.6 um to obtain a redox polymer material; 93 g of the redox polymer material, 3 g of carbon nanotubes, 2 g of carboxymethyl cellulose, 2 g of styrene-butadiene rubber and 200 g of water were mixed evenly, stirred for 20 hours, coated on an aluminum foil with a pole ear, and dried to obtain an anode.
[0065] Preparation of all-solid-state air battery:
[0066] The anode, perfluorosulfonic acid proton exchange membrane, platinum-carbon cathode and stainless steel filter gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0067] Example 9 Preparation of anode:
[0068] 100g of tannic acid and 14g of 37% formaldehyde are stirred and mixed evenly, and then 110g of concentrated sulfuric acid is added, stirred and mixed evenly, and heated to 90°C for reaction for 2h to obtain a reaction solution; 100mL of the reaction solution is added to 200g of porous alloy, stirred and kneaded, and after sufficient absorption and infiltration, heated to 110°C for curing, dried at 130°C, and then crushed to a particle size D50 of 8.9um to obtain a redox polymer material; 92g of the redox polymer material, 4g of conductive carbon black, 2.5g of carboxymethyl cellulose, 1.5g of styrene-butadiene rubber and 80g of water are mixed evenly, stirred for 12h, coated on an aluminum foil with a pole ear, and dried to obtain an anode.
[0069] Preparation of all-solid-state air battery:
[0070] The anode, perfluorosulfonic acid proton exchange membrane, platinum-carbon cathode and carbon fiber cloth gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.
[0071] The all-solid-state air batteries prepared in Examples 1 to 9 were subjected to performance testing, wherein the energy density and capacity retention rate were tested using a multi-channel battery tester, and a 103450 polymer battery purchased from Guangzhou Haoming New Energy Technology Co., Ltd. was used as a comparative example; the results are shown in Table 1.
[0072] Table 1 Performance test table of all-solid-state air batteries prepared in Examples 1 to 9
[0073] Energy density (mWh / g) 500-cycle capacity retention rate (%) Example 1 893 85.3 Example 2 914 85.5 Example 3 925 85.4 Example 4 973 85.5 Example 5 837 85.3 Example 6 918 86.3 Example 7 904 85.5 Example 8 877 85.1 Example 9 889 85.7 Comparative Example 205.5 83.2
[0074] It can be seen from the results in Table 1 that the all-solid-state battery of the present invention has a higher energy density than that of the comparative example, the energy density is greater than 800mWh / g, and the capacity retention rate of 500-cycle test is greater than 85%, and can be applied to energy storage, electric vehicles, electric ships, etc.
[0075] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.
Claims
1. An all-solid-state air battery, comprising a housing, an anode and a cathode, characterized in that: The anode and cathode are arranged in the housing; a proton exchange membrane is arranged between the anode and cathode, and the anode is connected to the cathode through a tab and a wire; the other side of the cathode is connected to a gas diffusion layer; The anode is made of a redox polymer material containing a phenolic hydroxyl group or a quinone group structure; The cathode is platinum carbon, palladium carbon, or a porous catalyst loaded with a platinum alloy or a palladium alloy.
2. The all-solid-state air battery according to claim 1, characterized in that: The gas diffusion layer is a carbon fiber cloth or a metal filter; the shell is provided with an air inlet and an air outlet; and the proton exchange membrane is a perfluorosulfonic acid proton exchange membrane.
3. The all-solid-state air battery according to claim 1, characterized in that: The anode is prepared according to the following method: 1) Mixing a phenolic hydroxyl-containing compound and an aldehyde-containing compound, adding an acid or base catalyst, stirring and mixing evenly, heating to 50-120° C. and reacting for 0.5-20 hours to obtain a reaction solution; 2) adding the reaction solution obtained in step 1) to the porous conductive material, stirring and kneading, and after sufficient absorption and infiltration, heating to 95-110° C. for curing, drying at 130° C., and then crushing to a particle size D50 of 2-20 μm to obtain a redox polymer material; 3) The redox polymer material, conductive agent, adhesive and water obtained in step 2) are uniformly mixed, stirred for 10 to 24 hours, coated on a copper foil or aluminum foil with a tab, and dried to obtain an anode.
4. The all-solid-state air battery according to claim 3, characterized in that: In step 1), the molar ratio of the phenolic hydroxyl-containing compound to the aldehyde-containing compound is 1-2:1-3.
5. The all-solid-state air battery according to claim 3, characterized in that: The phenolic hydroxyl compound in step 1) is one or two of phenol, hydroquinone, catechol, resorcinol, phloroglucinol, 1,2,4,5-pyrogallol, salicylic acid, gallic acid, tannic acid, biphenyldiol, biphenyltetraphenol, biphenylhexaphenol, naphthol, naphthalene diol and naphthalene tetraphenol; the aldehyde-containing compound in step 1) is one or two of formaldehyde, acetaldehyde and paraformaldehyde; the acid in step 1) is one or two of hydrochloric acid, phosphoric acid, sulfuric acid and oxalic acid; the base is one or two of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, ammonia water, urotropine, trimethylamine and triethylamine.
6. The all-solid-state air battery according to claim 3, characterized in that: The amount of the acid or base catalyst added in step 1) is 0.1 to 2 times the total mass of the phenolic hydroxyl-containing compound and the aldehyde-containing compound.
7. The all-solid-state air battery according to claim 3, characterized in that: The volume mass ratio of the reaction solution to the porous conductive material in step 2) is 0.2-1.5:1; the porous conductive material in step 2) is porous carbon or porous alloy.
8. The all-solid-state air battery according to claim 3, characterized in that: The mass ratio of the redox polymer material, the conductive agent, the adhesive and the water in step 3) is 85-95:1-5:1-5:50-200.
9. The all-solid-state air battery according to claim 3, characterized in that: In step 3), the conductive agent is one or two of conductive carbon black, conductive graphite, graphene and carbon nanotubes, and the binder is one or two of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile and polyacrylic acid.
10. The method for preparing the all-solid-state air battery according to claim 1, characterized in that: The following steps are involved: The anode, proton exchange membrane, cathode and gas diffusion layer are arranged in sequence, pressed tightly, placed in a casing and tightened to obtain an all-solid-state air battery.